Proposed E-Commerce Platform for Unredeemed Pawned Items - Kijkunasathian, Rasica; Suesaowaluk, Poonphon (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Purpose: This work proposes an online platform so called ePawnMart, which is designed specially for trading unredeemed pawned items to allows both the buyers and sellers to meet for accelerate the selling time, fair price of the pawned items for both side of customer and the shop owner. Research design, data and methodology: This study reviews available unredeemed pawned items selling methods, discusses main concerned areas to focus in building new e-commerce, and compare ePawnMart with the other existing platforms. The proposed system starts with the phase of system architecture, system requirements, use cases with use cases diagram, and main business flows with activity diagram. Results: Main features of the proposed platforms are discussed in detail both for buyers and sellers. Moreover, this study also proposes the user interface for both mobile app and websites of the proposed platform. This study does not include the real implementation of the proposed platform, which is recommended to be developed further in the future work. Conclusions: The proposed e-commerce platform would accelerate the growth of pawn shop industry by acting as a middleman who can help both the pawn shops (sellers) and buyers to solve their problems and get benefits.